Dunia Islam modern: Ensiklopedi Oxford - John L. Esposito (Mizan, 2001)
ir, jil.3,c.1/Oen, Jil.4=c.1/ws.jl.2.c.1/tr, jil.1=c.1; jil.2=c.2; jil.5=c.1; jil.6=c.1/stoc3=7 eks; Jl.1=c.2, jl.2=c.3, jl.3-6=c.2